Evaluation of some Antibiotics in Combination Activity Against Isolates of Staphylococcus aureus and Pseudomonas aeruginosa - Rammo, Rita N N (Al-Nahrain Journal of Science, 2018)
The combinations of eight first–line antibiotics were investigated against S. aureus and P. aeruginosa by the evaluation of fractional inhibitory concentration (FIC) index. Ten isolates of S. aureus and ten isolates of P. aeruginosa were isolated from clinical samples and the minimum inhibitory concentration (MIC) for each antibiotic was determined. Synergistic interactions were observed in the combinations ampicillin–gentamycin, rifampicin–neomycin and rifampicin–tetracycline against both S. aureus and P. aeruginosa; and also in ciprofloxacin-tobramycin for P. aeruginosa. Other combinations were either additive or indifferent; one antagonistic interaction between chloramphinicol–erythromycin was observed. The results suggest that antibiotic combination is a potential way to achieve synergy when the causal organism is a multi-antibiotic resistance one.